Potential Of Solid Waste Conversion Into Gelatin In The Fisheries Industry Of Indonesia - Priyosetyoko, Priyosetyoko; Widayat, W; Suzery, Meiny; Agustini, Tri Winarni (Indonesia Journal of Halal, 2022)
There has been an increase in aquaculture production in Indonesia from 2015 to 2019, which is 62.31%. Statistics Indonesia showed an increase in commodities for capture fisheries and aquaculture, namely 7.94% and 28.87%, while there was a decrease in fresh or cold fillet fish commodities, namely -6.89%, referring to data from January to June 2021 compared to the previous quarter of 2020. The development of fishery processing industries such as fish fillets, leaving waste in the form of skin, bones, fins, scales, heads, offal, and liquid. The remaining waste, if not managed properly, can have negative effects on the environment. One of the researches on the utilization of fish meat processing industrial waste is to make gelatin. Gelatin is a product of the hydrolysis of collagen from animal skin or bones. Gelatin from fish needs to be developed because it is a halal product. Gelatin hydrolysis can be carried out under acidic, alkaline, and enzymatic conditions. In the filtration process of making gelatin sheets, there is a by-product in the form of liquid gelatin. Research on the purification of polypeptides from gelatin from fish has been widely carried out. Polypeptides have benefits in the fields of cosmetics and medical health. In general, glycine in fish gelatin is higher than in mammals, while proline is the opposite. Research related to the purification of glycine from fish gelatin is interesting because it is viewed from the point of view of the benefits of biomolecular science and aspects of Indonesia's natural resources. Keywords: Waste; Gelatin; Polypeptides; Glycine